2014
DOI: 10.1105/tpc.114.125047
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Jasmonate-Dependent Defenses by Shade Involves Differential Regulation of Protein Stability of MYC Transcription Factors and Their JAZ Repressors in Arabidopsis

Abstract: Reduction of the red/far-red (R/FR) light ratio that occurs in dense canopies promotes plant growth to outcompete neighbors but has a repressive effect on jasmonate (JA)-dependent defenses. The molecular mechanism underlying this trade-off is not well understood. We found that the JA-related transcription factors MYC2, MYC3, and MYC4 are short-lived proteins degraded by the proteasome, and stabilized by JA and light, in Arabidopsis thaliana. Dark and CONSTITUTIVE PHOTOMORPHOGENIC1 destabilize MYC2, MYC3, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
206
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(216 citation statements)
references
References 95 publications
(137 reference statements)
8
206
0
2
Order By: Relevance
“…MYC2 accumulates during the day and is degraded during the night (Shin et al, 2012). MYC2, MYC3, and MYC4 are stabilized by light, via the action of red and blue light photoreceptors, and also by JA treatment (Chico et al, 2014). Phosphorylationdependent proteolysis of MYC2 was reported to be essential for its transcriptional activity (Zhai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MYC2 accumulates during the day and is degraded during the night (Shin et al, 2012). MYC2, MYC3, and MYC4 are stabilized by light, via the action of red and blue light photoreceptors, and also by JA treatment (Chico et al, 2014). Phosphorylationdependent proteolysis of MYC2 was reported to be essential for its transcriptional activity (Zhai et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For JAZ9, it was shown that nuclear localization is dependent on the interaction with the MYC2 transcription factor, and YFP-tagged JAZ9 accumulated in the cytosol in a myc2 mutant (Withers et al, 2012). MYC2, MYC3, and MYC4 are known to be short-lived proteins regulated by proteasomal degradation (Zhai et al, 2013;Chico et al, 2014). GFP-tagged MYC2 is largely removed from the cell in the dark and far-red light (Chico et al, 2014), and MYC2 protein levels oscillate over time under the control of the circadian clock (Shin et al, 2012).…”
Section: Jaz12 Interacts With Keg In the Cytoplasmmentioning
confidence: 99%
“…MYC2, MYC3, and MYC4 are very unstable proteins degraded by 26S proteasomes. MYC2 protein levels change in response to signals, e.g., circadian rhythm, methyl jasmonate (MeJA), and specific light conditions (Shin et al, 2012;Zhai et al, 2013;Chico et al, 2014). Dark, far-red light, shade, and CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) destabilize MYC2, MYC3, and MYC4, whereas MeJA, red light, and blue light stabilize them.…”
Section: Introductionmentioning
confidence: 99%
“…Dark, far-red light, shade, and CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) destabilize MYC2, MYC3, and MYC4, whereas MeJA, red light, and blue light stabilize them. Differential regulation of MYC2 stability by the change in the ratio of red to far-red light regulates JA-dependent defenses (Chico et al, 2014). TIME FOR COFFEE (TIC) represses MYC2 protein accumulation under the control of circadian clock.…”
Section: Introductionmentioning
confidence: 99%